Effect of ski boot settings on tibio-femoral abduction and rotation during standing and simulated skiing - Böhm, H.; Senner, V. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Ski boots are designed to transfer high forces from the skier to the ski. For this purpose, they are made of rigid materials and constrain the leg of the skier in an unnatural position. To overcome the problem of unnatural knee posture, the ski boots can be adjusted in the frontal plane, as well as in the horizontal plane, by the canting mechanism and the "v-position," respectively. Canting enables lateral and medial orientation of the shaft with respect to the base of the boot. The "v-position" is a pronounced outward rotation of the boot's base with respect to the ski's long axis. The purpose of this study is to investigate the effect of different foot rotations and ski boot canting settings on knee kinematics during standing and simulated skiing.